Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

Granite buried active faults detected by P- and S-wave reflection seismic imaging with integrated interpretation in urban areas of Beijing - Ketong Hu; Xu Liu; Rongyi Qian; Jun Zhang; Shuai Zhao; Xueheng Wang; Huayi Lin; Jianyu Ling; Qinghui Xie (Journal of Applied Geophysics, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Online probabilistic forecast of landslide failure time via multi-information fusion - Mingxi Chen; Penghui Lin; Jie Jiang; Xiaoduo Ou; Qinghui Jiang; Xiaojie Tan (Engineering Geology, 2026)

Policy-driven water quality trends in Qinhuangdao coastal waters, China (2003–2024): Nutrient controls and climate vulnerabilities via high-accuracy hue angle - Lin Wang; Xiang Wang; Xinxin Wang; Qinghui Meng; Zhijie Wang (Regional Studies in Marine Science, 2026)

Enzyme-treated Lotus seed powder matrix for curcumin delivery: From powder to tablet - Jiahai Shen; Xianwu Peng; Jiayi Fang; Qinghui He; Rufeng Luo; Yongjia Cai; Zonglin Guo; Jie Lin; Hua Zheng; Dingqiang Huang; Hongtao Lei; Shaozong Wu (Innovative Food Science & Emerging Technologies, 2026)

Effect of honey from fluid bed agglomeration to tableting of plant-based food powder: A case study of lotus seed powder - Xianwu Peng; Jiahai Shen; Rufeng Luo; Qinghui He; Weijuan Huang; Zonglin Guo; Jie Lin; Hua Zheng; Yijing Zhang; Dingqiang Huang; Hongtao Lei; Shaozong Wu (Food and Bioproducts Processing, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Humic acid and ferrihydrite weaken Cd release and resupply in high geological background soil assessed by DGT-DIFS - Dongqin LI; Zhendong PENG; Chunyan LIU; Yongtao LI; Jinjin WANG; Zhichao WU; Qinghui LIU; Furong LI; Hanzhi SHI; Dian WEN; Huayi CHEN; Xu WANG; et al. (Pedosphere, 2025)

Macrophyte community changes related to water level fluctuation and anthropogenic pressure in a floodplain lake in lower Huanghe River Basin, China since the 19th century - Qinghui Zhang; Yingying Chen; Shiyue Chen; Lin Liu; Enfeng Liu (Journal of Oceanology and Limnology, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Increased Nitrogen Application Alleviates Straighthead Disease by Reducing Dimethylarsinic Acid Accumulation and Promoting Mineral Nutrient Uptake in Rice - Qinghui Liu; Cuihua Bai; Weisheng Lu; Zhijun Zhang; Xueying Yin; Wanting Lin; Lixian Yao (Journal of Soil Science and Plant Nutrition, 2025)

Metal accumulation and contamination in sediments of 12 plateau lakes in Southwest China in response to human activities over the past century - Guozhan Li; Enfeng Liu; Enlou Zhang; Qinghui Zhang; Xiaoyu Wang; Wenke Chen; Hezhong Yuan; Jinkuo Lin (CATENA, 2025)

Local contributions and climate change effects on organochlorine pesticide levels in soil and sediments in Svalbard - Yan Lin; Geir Wing Gabrielsen; Zhibo Lu; Qinghui Huang; Peng Huang; Hongwei ke; Minggang Cai (Environmental Pollution, 2025)

ScRNA-seq and bulk RNA-seq identified NUPR1 as novel biomarkers related to CD4 + T cells infiltration for abdominal aortic aneurysm - Zhihao Zhou; Tang Deng; Suling Liu; Lin Huang; Kangjie Wang; Qinghui Kan; Rongzhou He; Chen Yao (Molecular Biology Reports, 2024)

Identification of Floating Green Tide in High-Turbidity Water from Sentinel-2 MSI Images Employing NDVI and CIE Hue Angle Thresholds - Lin Wang; Qinghui Meng; Xiang Wang; Yanlong Chen; Xinxin Wang; Jie Han; Bingqiang Wang (Journal of Marine Science and Engineering, 2024)
Remote sensing technology is widely used to obtain information on floating green tides, and thresholding methods based on indices such as the normalized difference vegetation index (NDVI) and the floating algae index (FAI) play an important role in such studies. However, as the methods are influenced by many factors, the threshold values vary greatly; in particular, the error of data extraction clearly increases in situations of high-turbidity water (HTW) (NDVI > 0). In this study, high spatial resolution, multispectral images from the Sentinel-2 MSI mission were used as the data source. It was found that the International Commission on Illumination (CIE) hue angle calculated using remotely sensed equivalent multispectral reflectance data and the RGB method is extremely effective in distinguishing floating green tides from areas of HTW. Statistical analysis of Sentinel-2 MSI images showed that the threshold value of the hue angle that can effectively eliminate the effect of HTW is 218.94°. A test demonstration of the method for identifying the floating green tide in HTW in a Sentinel-2 MSI image was carried out using the identified threshold values of NDVI > 0 and CIE hue angle 0), resulting in better consistency of the identification of the floating green tide and its distribution in the true color image. The method enables rapid and accurate extraction of information on floating green tide in HTW, and offers a new solution for the monitoring and tracking of green tides in coastal areas.

Inhibition of microelement accumulation and disorder of saccharide and amino acid metabolism explain rice grain empty under dimethylarsinic acid stress - Qinghui Liu; Zhijun Zhang; Cuihua Bai; Xueying Yin; Wanting Lin; Lixian Yao (Plant Cell Reports, 2024)

Retrieval and spatiotemporal variation of total suspended matter concentration using a MODIS-derived hue angle in the coastal waters of Qinhuangdao, China - Lin Wang; Xiang Wang; Qinghui Meng; Yanlong Chen; Xinxin Wang; Lingling Jiang; Yuhao Shang (Frontiers in Marine Science, 2024)
The CIE hue angle has significant potential in marine ecology and environment monitoring using remote sensing methods. It is calculated from the remote sensing reflectance ( R rs ) of all visible bands, which serves as a comprehensive indicator of seawater radiance information and represents one of the key quantitative parameters for assessing seawater color. In this study, a remote sensing retrieval model of total suspended matter concentration (TSM) was developed using the in situ measured data acquired in the coastal waters of Qinhuangdao from 2013 to 2021. This model, based on the CIE hue angle, achieved performance metrics of R 2 = 0.68, MAPE=24.47%, and RMSE=2.72 mg/L, demonstrating better accuracy than traditional empirical models that utilize fewer bands. Based on this model, the monthly and interannual TSM in the coastal waters of Qinhuangdao from 2003 to 2023 were retrieved. Influenced by natural factors, such as the monsoons, the TSM in the coastal waters of Qinhuangdao generally exhibited a trend of first decreasing and then increasing from January to December. Except for certain anomalous years (2007, 2008, 2017, etc.), the overall variation process of TSM from 2003 to 2023 showed an initial increase followed by a decrease, closely related to the pollution reduction management requirements implemented by the Chinese government in different periods. The findings of this paper demonstrate that the coastal waters of Qinhuangdao have become clearer, and the ecological environment has been effectively improved as a result of the Chinese government’s vigorous promotion of ecological civilization construction, adhering to the development concept that ‘lucid waters and lush mountains are invaluable assets’, and by introducing the action plan for the comprehensive treatment of pollution in the Bohai Sea.

5-Hydroxymethylfurfural mediated developmental toxicity in Drosophila melanogaster - Xunlin Chen; Qinghui Tu; Wenzheng Zhao; Xiaorong Lin; Zhongzheng Chen; Bin Li; Yuanyuan Zhang (Food and Chemical Toxicology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Straw incorporation induces rice straighthead disease in As-contaminated paddy soil - Qinghui Liu; Cuihua Bai; Zhijun Zhang; Xueying Yin; Wanting Lin; Yinghui Huang; Lixian Yao (Science of The Total Environment, 2023)

Simulation and measurement of the suction force on ellipsoidal seeds in an air-suction seed-metering device - Yongjie Wang; Wei Su; Qinghui Lai; Yuhong Lin; Junhong Li (Biosystems Engineering, 2023)

Genetic-simulated annealing optimization for surface wave inversion of shear-wave velocity profiles of geotechnical sites - Shibin Lin; Jeramy C. Ashlock; Guochen Zhao; Qinghui Lai; Longjun Xu; Changhai Zhai (Computers and Geotechnics, 2023)

Reproductive toxicity of polystyrene nanoplastics in Drosophila melanogaster under multi-generational exposure - Qinghui Tu; Jianhao Deng; Miaomiao Di; Xiaorong Lin; Zhongzheng Chen; Bin Li; Ling Tian; Yuanyuan Zhang (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

Blocking the 2,3-butanediol synthesis pathway of Klebsiella pneumoniae resulted in l-valine production - Qinghui Wang; Jinjie Gu; Lin Shu; Weiyan Jiang; Ljiljana Mojovic; Zorica Knezevic-Jugovic; Jiping Shi; Frank Baganz; Gary J. Lye; Wensheng Xiang; Jian Hao (World Journal of Microbiology and Biotechnology, 2022)

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

Effect of Different Glucose Concentrations on Small RNA Levels and Adherence of Streptococcus mutans - Shanshan Liu; Yan Zhou; Ye Tao; Peilin Zhuang; Liangyue Pang; Qinghui Zhi; Huancai Lin (Current Microbiology, 2019)

A Study on the Vibration Frequency of Blasting Excavation in Highly Stressed Rock Masses - Jianhua Yang; Wenbo Lu; Qinghui Jiang; Chi Yao; Shuihua Jiang; Lin Tian (Rock Mechanics and Rock Engineering, 2016)